Alprazolam Prompts HIV-1 Transcriptional Reactivation and Enhances CTL Response Through RUNX1 Inhibition and STAT5 Activation - Lin, Angel; Elbezanti, Weam Othman; Schirling, Alexis; Ahmed, Adel; Van Duyne, Rachel; Cocklin, Simon; Klase, Zachary (Frontiers in Neurology, 2021)
The HIV-1 pandemic is a significant challenge to the field of medicine. Despite advancements in antiretroviral (ART) development, 38 million people worldwide still live with this disease without a cure. A significant barrier to the eradication of HIV-1 lies in the persistently latent pool that establishes early in the infection. The “shock and kill” strategy relies on the discovery of a latency-reversing agent (LRA) that can robustly reactivate the latent pool and not limit immune clearance. We have found that a benzodiazepine (BDZ), that is commonly prescribed for panic and anxiety disorder, to be an ideal candidate for latency reversal. The BDZ Alprazolam functions as an inhibitor of the transcription factor RUNX1, which negatively regulates HIV-1 transcription. In addition to the displacement of RUNX1 from the HIV-1 5′LTR, Alprazolam potentiates the activation of STAT5 and its recruitment to the viral promoter. The activation of STAT5 in cytotoxic T cells may enable immune activation which is independent of the IL-2 receptor. These findings have significance for the potential use of Alprazolam in a curative strategy and to addressing the neuroinflammation associated with neuroHIV-1.